Prevalence estimates of mild behavioral impairment in a population-based sample of pre-dementia states and cognitively healthy older adults. (21st September 2017) - Mortby, Moyra E.; Ismail, Zahinoor; Anstey, Kaarin J.
ABSTRACT: Background: A dearth of population-based epidemiological research examines neuropsychiatric symptom (NPS) in sub-clinical populations across the spectrum from normal aging to mild cognitive impairment (MCI). The construct of mild behavioral impairment (MBI) describes the emergence of sustained and impactful NPS in advance of or in combination with MCI. This is the first epidemiological study to operationalize the recently published diagnostic criteria for MBI and determine prevalence estimates across the spectrum from cognitively normal to MCI. Methods: MBI was assessed in 1, 377 older (age range 72–79 years; 52% male; MCI ;= 133; cognitively normal, but-at-risk = 397; cognitively healthy = 847). MBI was assessed in accordance with the ISTAART-AA diagnostic criteria for MBI using the neuropsychiatric inventory. Results: 34.1% of participants met the criteria for MBI. High prevalence of MBI across the cognitive spectrum was reported (48.9% vs. 43.1% vs. 27.6%). Irrespective of level of cognitive impairment, impulse dyscontrol (33.8% vs. 28.7% vs. 17.2%) and decreased motivation (32.3% vs. 26.2% vs. 16.3%) were the most frequently met MBI domains. MBI was more prevalent in men (χ 2 = 4.98, p = 0.026), especially the domains of decreased motivation and impulse dyscontrol. Conclusions: This study presents the first population-based prevalence estimates for MBI using the recently published ISTAART-AA diagnostic criteria. Findings indicate relatively high prevalence of MBI in pre-dementia clinical states and amongst cognitively healthy older adults. Findings were gender-specific, with MBI affecting more men than women. Knowing the estimates of these symptoms in the population is essential for understanding and differentiating the very early development of clinical disorders.